Concept map as a teaching and learning tool for medical students - Sulakshana Shridhar Baliga; Padmaja Ravindra Walvekar; Girija Jagadish Mahantshetti (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND AND AIM: Concept maps hold great potential for the students as it helps in the formulation of new concepts as well to evaluate the learning ability of the students. However, the use of concept maps as a teaching tool in medical students in India has not been explored, to the best of our knowledge. This study was conducted to assess the use of concept maps in improving learning among medical students. MATERIALS And METHODS: This study was conducted among III MBBS students belonging to two batches. This study was carried out in two stages. In first stage, pretest was taken to test the knowledge of students. Later, introductory class was taken on tuberculosis and concept map was used to explain the given concept and later posttest was taken. In second stage, feedback was taken from the students regarding the concept map. Pre- and post-test results were compared using Wilcoxon test. RESULTS: Significant difference between pretest (4 ± 1.593) and posttest (10 ± 0.762) score was seen (P < 0.0001). More than 50% of students scored full marks in posttest, whereas no one got full marks in the pretest. Positive response (82.09%) was received from the students when feedback was taken regarding the use of concept map. CONCLUSION: Concept maps are found to be an effective teaching and learning tool for medical students. They can be used to enhance meaningful learning in students and can be practiced more in the students for better understandings of the concepts.